Mechanism and kinetics studies of the atmospheric oxidation of p, p'-Dicofol by OH and NO3 radicals. (March 2019) - Dang, Juan; Tian, Shuai; Zhang, Qingzhu
Abstract: As an effective organochlorine pesticide, Dicofol has been extensively applied in more than 30 countries for protecting over 60 different crops. Considering its large consumption and potential adverse effect on human health (endocrine disrupting and carcinogenicity), the fate of Dicofol sprayed into the air is of public concern. In this study, we conducted a comprehensive study on the reaction mechanisms of p, p' -Dicofol with OH and NO3 radicals using DFT method. Comparing the abstrations by OH and NO3 radical, OH and NO3 radical addition reactions are predominant due to the lower potential barriers and stronger heat release. The phenolic substances (P1P5), epoxides (P11 and P15), dialdehyde (P13) and other species (P8, P9, P10 and P14) are generated by OH additions and their subsequent reactions while OH abstraction reactions produce DCBP, P7 and chlorphenyl radical. Particularly, NO3 additions and their subsequent reactions yield dialdehydes (P16 and P17) and 2, 8-DCDD, which is the first report of the generation of dioxin from atmospheric oxidation of p, p' -Dicofol. Additionally, based on the structure optimization and energy calculation, rate constants and Arrhenius formulas of the elementary reactions of p, p' -Dicofol with OH and NO3 radicals were obtained over the temperature range of 280–380 K and at 1 atm. The rate constants for the reactions of p, p' -Dicofol with OH and NO3 radicals are 1.51 × 10 −12 and 8.88 × 10 −14  cm 3 molecule −1 s −1, respectively. The lifetime (τTotal ) of p, p' -Dicofol determined by the reactions of OH and NO3 radical is 5.86 h, indicating a potential long-range transport in the atmosphere. Graphical abstract: Image 1 Highlights: We studied a comprehensive mechanism of the reactions between p, p' -Dicofol and OH/NO3 radicals. The lifetime (τTotal ) of p, p' -Dicofol determined by the reactions with OH and NO3 radical is 5.86 h. NO3 addition and its subsequent reactions yield 2, 8-DCDD.